Computer-Aided-Design/Computer-Aided-Manufacturing Titanium Cranioplasty in a Child: Critical Appraisal. Issue 1 (January 2020) - Zegers, Thomas; Koper, David; Lethaus, Bernd; Kessler, Peter; ter Laak-Poort, Mariel
Abstract : Abstract: Large skull bone defects of the cranial vault can result from various reasons. Reconstruction of these defects is performed for protective and aesthetic reasons but is also required for adequate intracranial homeostasis. Computer-aided-design/computer-aided-manufacturing (CAD/CAM) patient-specific skull implants have become the most valuable alternative to the traditional methods of reconstruction and a growing number of publications is dealing with this topic in adults. Literature related to the application of these implants in pediatric cranioplasty is, however, still scarce. The authors present a case of a 9-year-old boy, where cranioplasty using a CAD/CAM additive manufactured titanium implant led to improvement of symptoms attributed to cerebrospinal fluid circulation problems and intracranial homeostasis disbalance. The authors further reflect on what the role of cranioplasty should be in the therapeutic treatment plan.